PFAS: challenges and scientific perspectives in human health risk assessment - Janine Kowalczyk; Klaus Abraham; Christina August; Runa S. Boeddinghaus; James C. Y. Chan; Alexander Eckhardt; Tony Fletcher; Finnian Freeling; Bernd Göckener; Thorhallur I. Halldórsson; Dorte Herzke; Ron L. A. P. Hoogenboom; et al. (Archives of Toxicology, 2026)
Abstract To review recent advances in research on per- and polyfluoroalkyl substances (PFAS) and outline priority steps for risk assessment in consumer health protection, the German Federal Institute for Risk Assessment (BfR) organized the ‘International PFAS Conference’ in Berlin in October 2025. Building on the European Food Safety Authority's (EFSA) opinion in 2020, global research activities on PFAS have intensified. The conference was attended by 200 participants from 18 countries and covered topics such as analytical methods, human exposure, toxicokinetics, toxicity, and future perspectives. Given that there are more than 21,000 different PFAS in use, discussions highlighted the need for further data collection and a basis for prioritizing substances. Robust exposure assessment requires improved analytical methods combined with newly developed predictive tools to quantify, identify, and make better use of non-target data. Hazard characterization may benefit from the combined use of classic experimental data sets, epidemiological data, and new approach methodologies (NAMs) data. The participants emphasized the continuous need for refined data and proposed a systematic consolidation of global data on shared data platforms, accompanied by corresponding guidelines for data usage. In the final panel discussion, effective risk communication was identified as a critical challenge, necessitating clear and consistent messaging for the public and policymakers. The conference concluded with five key recommendations for future health risk assessments: prioritizing PFAS; improving analytical methods; promoting generation of robust data and data gap filling; promoting open science, including the development of shared data infrastructure and cross-institutional knowledge exchange; and strengthening risk communication. These recommendations aim to support transparent, evidence-based and effective PFAS consumer health risk management in the decades ahead.